Weekly symptom profiles of nonhospitalized individuals infected with SARS‐CoV‐2 during the Omicron outbreak in Hong Kong: A retrospective observational study from a telemedicine center. Issue 2 (9th January 2023) - Luo, Jingyuan; Zhang, Jialing; Tang, Hiu To; Wong, Hoi Ki; Ma, Yanfang; Xie, Duoli; Peng, Bo; Lyu, Aiping; Cheung, Chun Hoi; Bian, Zhaoxiang
Abstract: Omicron BA.2.2 is the dominant variant in the Hong Kong outbreak since December 31, 2021. There is no study reporting the weekly symptom profile after infection. In this retrospective study, participants who tested positive for SARS‐CoV‐2 after December 31, 2021, and registered in the telemedicine system between March 14 and May 6, 2022, were analyzed. Among registered 12 950 self‐quarantined COVID‐19‐positive patients, 11 776 symptomatic patients were included for weekly symptom profile analysis. A total of 4718 (40.1%) patients reported symptoms in the first week after a positive test, 2501 (21.2%) in the second week, 1498 (12.7%) in the third week, 1048 (8.9%) in the fourth week, and 2011 (17.1%) in over 4 weeks. Cough was the most common symptom in all participants. Patients in the first week had higher odds of reporting fever (0.206, 95% confidence interval [CI]: 0.161–0.263, p < 0.001) and sore throat (0.228, 95% CI: 0.208–0.252, p < 0.001). Patients in over 4 weeks had higher odds of reporting fatigue (1.263, 95% CI: 1.139–1.402, p < 0.001). Further, having at least two vaccine doses linked to lower odds of having fever (0.675, 95% CI: 0.562–0.811, p < 0.001), but not associated with the presence of cough and fatigue. Diabetic patients had higher odds of reporting diarrhea (1.637, 95% CI: 1.351–1.982, p < 0.001). Symptoms from Omicron infection may last for more than 4 weeks and symptom profiles vary from week to week. Vaccination and comorbidity affect the symptom profiles.